Evaluating the effects of Hong Kong-Zhuhai-Macao bridge on international air travel: demand analysis of the air-bridge-air path. (19th May 2020) - Lu, Jing; Lv, Cheng; Feng, Tao; Wang, Zheqing
To consolidate its position as the busiest Chinese hub to Southeast Asia, Hong Kong airport is collaborating with Zhuhai airport through the Hong Kong-Zhuhai-Macao Bridge to establish an air-bridge-air path, which may potentially encourage the international business and tourism along the Belt and Road economic corridor. To predict the increased demand attracted by this path, this paper proposes a path choice model using a nested logit model, which incorporates intermodal transfers on a time-space network. The proposed model was estimated based on the data collected from a stated preference survey and was applied to forecast the geographical distribution of air passenger flow. As predicted, the air-bridge-air path improves the connection and the travel efficiency between Northwest China and Southeast Asia, indicating its contribution to develop the Belt and Road initiative. Meanwhile, some strategies for developing the flight network of Zhuhai airport are proposed, where starting up a new air route from Xining to Zhuhai is recognised as the best option according to the scenario analysis results.